Evaluation of Novel Dry Eye Model: Preganglionic Parasympathetic Denervation in Rabbit - Toshida, Hiroshi (2007)
PURPOSE: To evaluate ocular surface status after interruption of preganglionic, parasympathetic neural control after surgical removal of the greater superficial petrosal nerve (GSPN). METHODS: New Zealand White rabbits underwent unilateral section and removal of a 5-mm portion of the GSPN by a route through the inner ear; no ocular or orbital tissue was involved. Before and 7 days after surgery, all animals underwent preliminary examination, including fluorescein staining, rose bengal instillation, blink rate, tear breakup time (BUT), tear flow, and impression cytology. Total tarsorrhaphy was carried out in four additional rabbits, and another four animals underwent unilateral sham procedures. The GSPN, pterygopalatine ganglion, lacrimal gland, and conjunctiva were evaluated by light and transmission electron microscopy (TEM). RESULTS: GSPN sectioning resulted in significant changes of the ocular surface after 7 days: intense rose bengal staining of the conjunctiva, fluorescein staining of the cornea, increased blink rate (P < 0.05), decreased BUT (P < 0.005), decreased tear flow by 26% (P < 0.005), and decreased goblet cell density (P < 0.01). TEM revealed massive accumulation of secretory granules in lacrimal acinar cells. The changes were also seen after tarsorrhaphy. Neither the contralateral control nor the sham eyes were affected. CONCLUSIONS: The effects of GSPN nerve section led to the rapid onset of a dry eye condition in the rabbits that continued for at least 1 week. The authors suggest that continuous neural drive of the pterygopalatine ganglion is necessary to maintain adequate tear flow and mucin secretion. It is likely the trigeminal system is the afferent origin of this continuous neural tone.